Domestic refrigerator temperatures in Spain: Assessment of its impact on the safety and shelf-life of cooked meat products. (December 2019) - Jofré, Anna; Latorre-Moratalla, Mari Luz; Garriga, Margarita; Bover-Cid, Sara
Abstract: Temperature is one of the main factors governing the growth of microorganisms. The aim of the present study was to provide temperature conditions representative of the food products stored in domestic refrigerators and to assess the impact of the temperature (fluctuation) on the shelf-life of refrigerated cooked meat products, from the safety and the spoilage point of view. The analysis of the time-temperature profiles recorded from 160 domestic refrigerators of households from small (28%) and large (72%) municipalities in Catalonia (Spain) showed that the 24 h-mean temperature could be described by a normal distribution (mean = 5.4 °C, standard deviation = 2.3 °C) with a mean value within the upper limit of the appropriate storage temperature of refrigerated products (i.e. ≤6 °C). The impact of door openings or day and night was not significant. Temperature distribution showed differences depending on the season, being higher in the cold season than in the warm one. Noteworthy, refrigerators of elderly (≥ 65 years old) households showed a higher percentage of time at temperatures >8 °C in comparison with those of the general population. Overall, the 75th percentile of the distribution of the 24 h-mean temperature values was 6.7 °C. This study can be used as a scientific evidence of the consumer storage stage when food business operators or laboratories conduct shelf-life studies. According to the simulation of the growth of Listeria monocytogenes and lactic acid bacteria in cooked meat products, risk scenarios were identified in which the critical level of the pathogen could be reached before lactic acid bacteria achieved the spoilage level. The fluctuation of the refrigerator temperature ranged from 0.5 up to 12.2 °C within the 24 h-profile. The assessment of the safety of cooked meat products stored at constant temperature or under different time-temperature profiles showed that both the mean and the fluctuation of the profile had an impact on the shelf-life, which was higher at low temperatures. The improvement of the household refrigerated storage would be an effective way to increase food safety of refrigerated ready-to-eat food. Graphical abstract: Unlabelled Image Highlights: The mean 24 h-mean temperature of 160 surveyed domestic refrigerators was 5.4 °C. The study indicates 6.7 °C as the 75th percentile for consumer storage stage. Risk scenarios where L. monocytogenes develops before LAB spoilage were identified. Temperature fluctuation negatively affects the safety of RTE products.